Successful Treatment of Recurrent Pustular Psoriasis of Pregnancy with Secukinumab: A Case Report - Na Liu; Lin Zhu; Yuanyuan Cheng; Ning Yu; Xuemei Yi; Yangfeng Ding (Medical Journals Sweden, 2020)
Abstract is missing (Short Communication)